Leber’s Hereditary Optic Neuropathy: A Case Misinterpreted As Optic Neuritis - Dhaivat Shah; Tina Damani; Shirali Gokharu; Akshar Soni (Delhi Journal of Ophthalmology)
A 38 year old male presented with bilateral complete loss of vision over 1 year, left followed by right eye. He was diagnosed to have optic neuritis and was given treatment accordingly, with no improvement in vision. After clinical examination and MRI testing, we diagnosed him to have LHON, explained him the guarded course and nature of the disease and advised gene testing. LHON is a diagnosis of exclusion, and often confused with other optic neuropathies. A sound history, astute clinical examination and appropriate testing can diagnose this rare condition.